Toxicological studies of pesticide formulations imidacloprid and malathion on albino mice - Walid Said Helmy; Amal Yousef Saleh; Essam Eldin Abdelraouf Eweis (Cairo : Walid Said Helmy, 2014)
The toxicity of imidacloprid (in two formulations Gaucho 70% WP and Confidet 35% SC and malathion El Nasr and Kafr El Zayat 57 % EC) was investigated on male albino mice using 1/8, 1/4 and 2/5 oral sub-lethal doses of LD50 in plasma, brain, liver and kidney for 24 and 48 hrs. Confidet caused a decrease in total protein content in plasma, brain, liver and kidney at of 1/8, 1/4 and 2/5 LD50 doses versus an increase in total protein when using the same concentrations of Gaucho after 24 and 48 hrs. Confidet further inhibited the cholinesterase in plasma at 1/8, 1/4 and 2/5 of LD50 doses after 24 and 48 hrs while treatment with Gaucho increased the activity of the same enzyme. The activity of aspartate aminotransferees in plasma increased after treatment with 1/8, 1/4 and 2/5 LD50 in both Confidet and Gaucho but the rate of increase of activity was greater in Gaucho than Confidet, meanwhile enzyme activity decreased in liver in the cases of treatment with both formulations but the rate of decrease activity for Confidet was greater than it in the case of Gaucho
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Pesticides
Issued also as CD
Keywords: Aspartate aminotransferase; Cholinesterase; Imidacloprid